2017
DOI: 10.33549/physiolres.933811
|View full text |Cite
|
Sign up to set email alerts
|

Mutant Wars2 Gene in Spontaneously Hypertensive Rats Impairs Brown Adipose Tissue Function and Predisposes to Visceral Obesity

Abstract: Brown adipose tissue (BAT) plays an important role in lipid and glucose metabolism in rodents and possibly also in humans. Identification of genes responsible for BAT function would shed light on underlying pathophysiological mechanisms of metabolic disturbances. Recent linkage analysis in the BXH/HXB recombinant inbred (RI) strains, derived from Brown Norway (BN) and spontaneously hypertensive rats (SHR), identified two closely linked quantitative trait loci (QTL) associated with glucose oxidation and glucose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…These single-nucleotide polymorphisms (SNPs) are associated with the waist-hip ratio in human genome-wide association studies, which are explained by changes in adipose tissue distribution ( Heid et al., 2010 ). Our studies support the possibility that WARS2 is one of the effector genes in this association locus ( Pravenec et al., 2017 ).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These single-nucleotide polymorphisms (SNPs) are associated with the waist-hip ratio in human genome-wide association studies, which are explained by changes in adipose tissue distribution ( Heid et al., 2010 ). Our studies support the possibility that WARS2 is one of the effector genes in this association locus ( Pravenec et al., 2017 ).…”
Section: Discussionsupporting
confidence: 86%
“…Genetic mapping in the rat for coronary flow and capillary density traits in the heart identified a causal missense variant in Wars2 that reduced WARS2 activity by ∼40% ( Wang et al., 2016 ). It was also shown that the mutation reduced endothelial cell proliferation and activated pro-apoptotic pathways, as well as impairing BAT function ( Pravenec et al., 2017 , Wang et al., 2016 ). Finally, Wang et al.…”
Section: Discussionmentioning
confidence: 99%
“…WARS2 encodes a mitochondrial tryptophanyl tRNA synthetase that has been linked to mitochondrial-related neurodegeneration [ 30 ]. One study suggested that increased WARS2 expression is associated with decreasing visceral adiposity through effects on brown adipose tissue function [ 31 ]. It is unclear which of the many obesity-associated SNPs in the TBX15/WARS2 region or eBMD-detected SNPs at the TBX15 locus are biologically relevant to obesity or osteoporosis.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these advanced QTL mapping strategies developed in rats, RI and HS strains have also contributed to quantitative genetic studies. These rat strains have been used to detect QTLs [48][49][50][51][52][53][54][55][56][57][58][59][60][61] for 1) cardiovascular conditions, such as blood pressure, electrocardiographic parameters, basal mean arterial pressure (MAP), delta MAP and delta heart rate, left ventricular hypertrophy and heart size; 2) metabolic complexity, such as alcohol consumption and propensity for alcohol-induced organ damage, glucose oxidation and its incorporation into brown adipose tissue lipids, insulin resistance, dyslipidemia and glucose handling; 3) behavioral traits, such as shuttle box, automated novel cage activity and elevated zero maze, startle motor response and habituation, anxiety and locomotion traits associated with elevated plus maze, and conditioned taste aversion; 4) physiologic and hormonal quantitative traits, such as serum adiponectin and thyroid stimulating hormone activity, dopamine betahydroxylase enzyme activity, catecholamine biosynthesis and catecholamine secretion; 5) bone fragility, bone mineral density, bone structure and bone strength; 6) hematology, such as full blood count; 7) immunology, such as FACScan analysis of white blood cells; 8) neuroinflammation, such as myelin oligodendrocyte glycoprotein induced experimental autoimmune encephalomyelitis and TNF alpha in serum; and 9) tissue weight, such as adrenal glands, bone, blood, brain, ears, heart, kidney, liver, spinal cord, spleen, and thymus. In addition, Szpirer [62] recently reviewed the use of rats for knockout investigations of QTLs and gene functions.…”
Section: Genome Variationmentioning
confidence: 99%